Implementation of Orthopedic Surgery in Hospitals During the Covid-19 Pandemic: A Literature Review - Puspitowarno Puspitowarno; Arlina Dewi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The spread of COVID-19 through the air has prompted adjustments in the orthopedic field by delaying elective surgical treatment to reduce the burden on the health system and allow more beds to be made available for those in need so that hospital services are optimal. This research aims to determine the implementation of orthopedic surgery services in hospitals during the COVID-19 pandemic. This literature review uses articles in the PubMed, Google Scholar, and ProQuest databases published in 2019-2020, in full text, in English, using the keywords orthopedic AND COVID-19 AND emergency department OR trauma service. The researcher obtained 191 articles and then reviewed them using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) diagram and The Joanna Briggs Institute (JBI) Critical Appraisal instrument. Seven articles were eligible for analysis. During the COVID-19 pandemic, orthopedic surgery services were limited to only allowing emergency surgery. Orthopedic specialists are also empowered to screen and examine suspected COVID-19 patients. Surgery is only performed by an exceptional team and outside working hours. This study shows a change in orthopedic services in hospitals during the COVID-19 pandemic. Abstrak: Penularan penyakit COVID-19 melalui udara mendorong penyesuaian di bidang ortopedi dengan penundaan perawatan bedah elektif untuk mengurangi beban sistem kesehatan dan memungkinkan tersedianya lebih banyak tempat tidur bagi mereka yang membutuhkan,  sehingga pelayanan rumah sakit menjadi optimal. Tujuan literatur review ini untuk mengetahui pelaksanaan pelayanan terkait bedah ortopedi di rumah sakit selama masa pandemi COVID-19. Literature review ini menggunakan artikel pada database PubMed, Google Scholar, dan ProQuest yang diterbitkan pada 2019-2020, memiliki teks lengkap, berbahasa Inggris, menggunakan kata kunci ortopedic DAN COVID-19 DAN emergency department ATAU trauma service. Didapatkan  191 artikel kemudian direview menggunakan diagram Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) dan menggunakan instrumen The Joanna Briggs Institute (JBI) Critical Appraisal, mendapat 7 artikel yang memenuhi syarat untuk dianalisis. Selama masa pandemi COVID-19, layanan bedah ortopedi dibatasi dengan hanya mengizinkan operasi darurat. Spesialis ortopedi juga diberdayakan untuk melakukan skrining dan memeriksa pasien suspek COVID-19. Pembedahan hanya dilakukan oleh tim khusus dan dilakukan di luar jam kerja. Prosedur ortopedi yang menghasilkan aerosol akan dibatasi dan jumlah operator dalam satu ruang operasi dikurangi. Penanganan pasien ortopedi di klinik rawat jalan dapat dilakukan secara virtual. Penelitian ini menunjukkan bahwa terdapat perubahan pola pelayanan ortopedi di rumah sakit selama pandemi COVID-19.